Sosialisasi Hasil Penelitian Respon Pertumbuhan Rumput Hijauan Setaria Sphacelata Terhadap Pemberian Pupuk Cair Urin Kambing Terfermentasi Pada Tahun 2024 - Hadirin, Hadirin; Zendrato, Desti Prestasi; Joharsah, Joharsah; Kartono, Kartono; Syahputra, Muahmmad Ary; RS, Muttaqinullah; Arwinsyah, Arwinsyah (Mitra Abdimas: Jurnal Pengabdian kepada Masyarakat, 2024)
This study aimed to evaluate the growth response of Setaria sphacelata forage grass to the application of fermented goat urine liquid fertilizer. The experiment employed a factorial design with two factors: doses of fermented goat urine liquid fertilizer (0, 10, 15, and 20 liters/ha) and forage type (Setaria sphacelata). Parameters measured included tiller number, plant height, fresh and dry matter production, and phosphorus and potassium content. Results indicated that the application of fermented goat urine liquid fertilizer significantly affected (P<0.05) all measured parameters. Increasing doses of fermented goat urine liquid fertilizer generally enhanced the growth and production of Setaria sphacelata. The optimal dose of fermented goat urine liquid fertilizer for Setaria sphacelata was 15 liters/ha, although the best results were obtained at 20 liters/ha. This study concludes that the use of fermented goat urine liquid fertilizer effectively improves the growth and production of Setaria sphacelata forage grass, with the best combination observed at a dose of 20 liters/ha.